Impacts of Regional Economic Factors on the Transmission of Coronavirus Disease 2019 (COVID-19) in Indonesia - Estro Dariatno Sihaloho; Wiksadana Wiksadana; Cavin Dennis Tito Siregar (Ekonomis: Journal of Economics and Business, 2020)
With 194,109 cases on 6th September 2020, Indonesia is one of the most infected countries of COVID-19. The daily total number of new confirmed COVID-19 cases passed the 3,000 mark for the first time since the beginning of the pandemic, with 3,003 and 3,308 new cases reported on 28 and 29 August, respectively. Jakarta and East Java mainly contributed to the surge, while several provinces like West Java, North Sumatera, and East Kalimantan emerged as new hotspots. With the high growing case number, this research seeks to analyze the linkages between the regional economic situations and each COVID 19 cases in Indonesia. This research analyzes the effect of regional economic through the number of poverties in urban and rural areas, the hotel room occupancy rate, the Gini Ratio in both urban and rural areas. The cross section data variables are selected from the data in 2020 within 34 provinces in Indonesia from Badan Pusat Statistika Indonesia and Gugus Tugas Percepatan Penanganan COVID-19 Indonesia. This paper also plot and analyze some province level data in 2019. The analysis indicates that poverty in rural and urban areas, hotel room occupancy rate, and Gini Ratio in Urban Area have positive and significant impact on the total COVID-19 cases. The plot analysis show that population density, percentage of households in urban slum, percentage of household frequency of using used water for other purposes have positive relation with transmission of COVID-19 in Indonesia. Until 6th September 2020, the transmission of COVID-19 in Indonesia is increasing rapidly. In regards of this situation, the government should have imposed stricter regulations in the mandatory mask in public spaces, social distancing, and other preventive measures in all provinces in Indonesia.